Who takes a break? Profiles, motives, and implications for sustainable careers - Mendoça, M.; Sousa, I.C. (17th EAOHP Conference, 2026)
Background: As population ageing, intensifying labour shortages, and technological advancements challenge traditional models of career development, promoting sustainable careers has become a strategic priority for organisations. Sustainable careers are dynamic, evolving trajectories shaped through a cyclical, self-regulatory process in which individuals interpret and respond to positive and negative experiences (De Vos et al., 2020). They prioritise productivity, engagement, and well-being over time while adapting to internal and external changes. Career breaks have been introduced as an initiative to support people in voluntarily stepping away from their jobs temporarily. However, research on career breaks remains scarce, focusing mostly on breaks related to maternity among women. The goal of this study was to identify profiles of workers who have already taken career breaks, exploring their main reasons and consequences. Method: A sample of 78 participants aged between 21 and 72 years (M = 41.0, SD = 13.4) completed an online survey between March and April 2025. Of these, 73.1% were female, 44.9% had completed a bachelor’s degree, and 50.0% had completed postgraduate studies. A cluster analysis (TwoStep Cluster) was carried out to identify profiles, a chi-square test was used to examine the main reasons for taking breaks, and a one-way ANOVA was conducted to analyse the consequences of breaks. Results: Three clusters were identified. Cluster 1, called “Young Starters” (32.4% of the sample), is characterised by younger, less experienced workers in early career stages, with few or no dependents. Cluster 2, named “Seasoned Veterans” (29.6% of the sample), comprises older, highly experienced workers in late or advanced career stages, typically with about one dependent. Cluster 3, called “Mid-Career Balancers” (38.0% of the sample), includes middle-aged workers with moderate experience, in mid-career stages, and one to two dependents. The Silhouette coefficient was between 0.5 and 1.0, indicating good cluster separation. The chi-square test showed no significant association between profiles and motives for career breaks. Still, “Young Starters” most frequently cited health and well-being (33.3%) and education and training (23.8%) as their main motives, while “Seasoned Veterans” and “Mid-Career Balancers” primarily chose family support (60.0% and 51.9%, respectively). No significant differences were found between the three profiles regarding the perceived impacts of career breaks on happiness, health, and productivity (the three dimensions of sustainable careers). Nevertheless, “Seasoned Veterans” reported higher happiness (4.43) than “Mid-Career Balancers” (4.15) and “Young Starters” (4.26), and greater productivity (4.05) than “Mid-Career Balancers” (3.74) and “Young Starters” (3.78). Perceptions of health were very similar across profiles (“Seasoned Veterans” = 4.33, “Mid-Career Balancers” = 4.33, “Young Starters” = 4.22). Conclusion: Career breaks represent an important initiative for supporting sustainable careers and can be used by different profiles of workers, reflecting their diverse personal and professional motives. Regardless of profile, career breaks appear to have positive impacts on the happiness, health, and productivity of those who take them. Although this study did not fully account for the complexity of workers’ life stages, longer and more sustainable careers depend on opportunities such as career breaks, which organisations can facilitate when requested by employees.